Insertions in the Reverse Transcriptase Increase both Drug Resistance and Viral Fitness in a Human Immunodeficiency Virus Type 1 Isolate Harboring the Multi-Nucleoside Reverse Transcriptase Inhibitor Resistance 69 Insertion Complex Mutation - Quiñones-Mateu, Miguel E. (American Society for Microbiology, 2002)
Recent studies have shown that the accumulation of multiple mutations associated with nucleoside reverse transcriptase inhibitor (NRTI) resistance may be grouped as multi-NRTI resistance (MNR) complexes. In this study, we have examined the viral fitness of recombinant viruses carrying the reverse transcriptase (RT) of a human immunodeficiency virus type 1 (HIV-1) primary isolate harboring mutations comprising the MNR 69 insertion complex. Different RT mutants were prepared in the sequence context of either the wild-type RT sequence of the HIV-1(BH10) isolate or the sequence found in a clinical HIV-1 isolate with the MNR 69 insertion mutation. As expected, in the presence of zidovudine, recombinant viruses harboring the MNR RT from the patient were more fit than wild-type viruses. However, in the absence of drug, the virus with the RT from the original clinical isolate (SS) was more fit than (i) the wild-type virus with an engineered serine insertion between residues 69 and 70 (T69SSS) and (ii) the recombinant virus with the MNR RT where the insertion was removed (2S0S). These results suggest that RT insertions, in the right sequence context (i.e., additional mutations contained in the MNR 69 insertion complex), enhance NRTI resistance and may improve viral fitness. Thus, comparing complex mutation patterns with viral fitness may help to elucidate the role of uncharacterized drug resistance mutations in antiretroviral treatment failure.